Missing Marx: The Place of Marx in Current Communication Research and the Place of Communication in Marx’s Work - İrfan Erdogan (tripleC: Communication, Capitalism & Critique)
This study was designed (1) to test Marx’s theoretical statements on the nature of dominant ideas in a society by investigating the character of scholarly practices in academic publishing, and (2) to demonstrate the falseness of claims about Marx’s disinterest in communication by presenting and evaluating his writings on communication. The study combines quantitative and qualitative methods for data collection and analysis. It has two study populations and multiple samples. The first one includes the articles in communication journals cited by Thomson Reuters’ Social Sciences Citation Index. The second one contains all writings of Marx on communication. The findings indicate that (1) the articles are mostly functional to the ruling interests, (2) they mostly exclude Marx and critical issues that question the ruling material and immaterial mode and relations in communication and society, (3) most alternative approaches are controlled alternatives and overtly or covertly directed against Marx’s method and explanations. Regarding Marx’s interest in communication, contrary to the claims that he had no or minimal interest, Marx provided invaluable explanations about communication. Hence communication scholars should pay close attention if they want to understand the nature and function of communication in society and social change.